Mechanism study on the enhancement of bile acid-binding capacity in corn by-product juice via Lactiplantibacillus plantarum HY127 fermentation - Huanyong Lv; Xiaohui Tang; Jian Zhang; Menghan Ma; Xinyi Li; Zhenjie Zheng; Yunhe Xu; Lili Zhang (Food Chemistry: X)
Hyperlipidemia is a common endocrine metabolic disease in humans. Long-term medications often have adverse effects, making the search for safer and more effective treatments crucial. This study aimed to explore the impacts and mechanisms of Lactiplantibacillus plantarum HY127 fermentation on enhancing bile acid-binding capacity (BABC). We fermented corn by-product juice (CBJ) by HY127 and investigated the BABC of HY127 bacterial cells and their metabolites. Our results indicated that HY127 cells (95.25 %) played a major role in enhancing BABC, with metabolites (31.50 %–66.41 %) also contributing. Compared to unfermented CBJ, the contents of phenolics, flavonoids, polysaccharides, and organic acids were significantly higher. Non-targeted metabolomics revealed upregulated amino acids, alkaloids, terpenoids, and other bioactive substances associated with BABC in the supernatant. This study confirmed that HY127 fermentation enhances the BABC of CBJ (increased by 32.02 %–78.76 %), providing a research foundation and technical reference for the development of LAB-fermented corn by-product beverages with hypolipidemic activities.